Closed-Form Equation of Data Dependent Jitter in First Order Low Pass System - Sangjin Byun (The Scientific World Journal)
This paper presents a closed-form equation of data dependent jitter (DDJ) in first order low pass systems. The DDJ relates to the system bandwidth, the bit rate, the input rise/fall time, and the number of maximum consecutive identical bits of the data pattern. To confirm the derived equation, simulations have been done with a first order RC low pass circuit for various system bandwidths, bit rates, input rise/fall times, and data patterns. The simulation results agree well with the calculated DDJ values by the derived equation.